Methodology of Measuring Motoric Cognitive Risk Syndrome—Focusing on Slow Gait Speed: Protocol for a Systematic Review - Su, Liming; Sun, Xue; Huang, Cheng; Wei, Zhuqin; Shen, Xinhua; Wang, Lina (Frontiers in Psychiatry, 2022)
Introduction: Older adults with motoric cognitive risk (MCR) syndrome are at high risk of developing dementia. Although the definition of MCR is well recognized and consensus, previous studies did not reach an agreement on diagnostic criteria and measurement methods/tools for slow gait speed, which is one of four components of MCR diagnosis. The substantial heterogeneity in the methodology of slow gait speed diagnosis for MCR limits comparability and meta-analysis of studies. Objective: The study aims to conduct systematic and standardized integration for diagnostic criteria and methods of slow gait speed diagnosis for MCR based on previous evidence that may improve comparability between future studies. Methods: A systematic literature review will be undertaken by searching the following electronic databases (until February 1, 2022): PUBMED, EMBASE, The Cochrane Library, Web of Science. Additional studies will be identified by checking the reference lists of included studies or relevant reviews, manually searching the Internet and Google Scholar, and searching the authors’ personal files, if necessary. Two investigators will perform data extraction independently, and discrepancies will be resolved by discussion, which will include a third investigator if requires. The paper selection will perform in duplicate. Finally, a narrative account will synthesize the findings to answer the objectives of this review. Discussion: This is the first study on systematic and standardized integration for diagnostic criteria and measurement methods/tools for slow gait speed in diagnosing MCR. The findings of this study will be convenient for medical staff to examine the intended use and applicability of each instrument/tool for evaluating the gait speed and provide insight into developing uniform guidelines for MCR. Systematic Review Registration: PROSPERO registration number: CRD42021232671.